Vom "Türkenjoch" zu "Deutschlands Freundschaft für die Türkei" Der Wandel des Wissens über das Osmanische Reich in deutschen Geschichtsschulbüchern 1839-1918 - Hellmanzik, Timm Gerd (Wie die Türken in unsere Köpfe kamen. Eine deutsche Bildungsgeschichte, 2023)
The change of saying "From the Turkish yoke" to "Germany's friendship for Turkey" shows the changed perception of the Ottoman Empire in German history textbooks of the 19th and early early 20th century. This book offers comprehensive insights into historical textbook texts and their ways of representing "Turks" and "Turkey", which have hardly been taken into account in research on the history of education. It documents the interplay of images of the self and the other within the the pedagogical discourse of the time from a transnational and transnational and postcolonial perspective.